2006
DOI: 10.4028/www.scientific.net/msf.527-529.1079
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Deposition of HfO<sub>2</sub> Gate Insulator on SiC by Metalorganic Chemical Vapor Deposition

Abstract: Low temperature deposition of HfO2 films on 4H-SiC(0001) substrates by pulse introduced metalorganic chemical vapor deposition (MOCVD) using tetrakis-diethylamido-hafnium [Hf[N(C2H5)2]4, (TDEAH)] and H2O has been investigated. HfO2 films with relatively low leakage current density of 10-4 A/cm2 were obtained even at a deposition temperature as low as 190 °C. We demonstrate that the HfO2/SiC interface, where the HfO2 was deposited at 190 °C, has lower interface state density than a typical thermally-grown SiO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We observe clear deposition temperature dependence. We have previously characterized HfO 2 /SiC interface properties and have reported that SiC can be oxidized during the oxide deposition even at low temperature of 400 o C which degrade HfO 2 /SiC electrical properties [7]. Hence, it can be considered that the low temperature deposition of Al 2 O 3 effectively suppressed the oxidation of SiC substrate and resulted in a good interface property.…”
Section: Resultsmentioning
confidence: 99%
“…We observe clear deposition temperature dependence. We have previously characterized HfO 2 /SiC interface properties and have reported that SiC can be oxidized during the oxide deposition even at low temperature of 400 o C which degrade HfO 2 /SiC electrical properties [7]. Hence, it can be considered that the low temperature deposition of Al 2 O 3 effectively suppressed the oxidation of SiC substrate and resulted in a good interface property.…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, all of the reported techniques were purely concentrated on methods such as metalorganic chemical vapor deposition, atomic layer deposition (ALD), pulsed laser deposition (PLD), and others, except for sol-gel method [7][8][9]. In contrast, sol-gel technique has been employed to deposit HfO 2 film on Si [10,11] due to its relatively low cost and simple deposition technique.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, to avoid the formation of interface states, many attempts to use a deposited oxide as a gate insulator of the SiC MOS devices were reported [1,2]. We have previously reported excellent performance in 4H-SiC MOSFETs with Al 2 O 3 gate insulator which was deposited at as low as 190 o C by metal-organic chemical vapor deposition (MOCVD) [3][4][5][6] . In the previous work, we used triethyl-aluminum (TEA) and H 2 O as precursors and demonstrated that the peak value of field-effect-mobility was approximately 60 cm 2 /Vs when the Al 2 O 3 gate insulator was deposited on HF-treated 4H-SiC (0001) substrate with TEA and H 2 O at 190 o C [3].…”
Section: Introductionmentioning
confidence: 99%